Lipoprotein-Associated Phospholipase A2 Activity Is Associated With Risk of Coronary Heart Disease and Ischemic Stroke: The Rotterdam Study - Oei, Hok-Hay S.; van der Meer, Irene M.; Hofman, Albert; Koudstaal, Peter J.; Stijnen, Theo; Breteler, Monique M.B.; Witteman, Jacqueline C.M. (Circulation (New York, N.Y.), 2005)
Background— Lipoprotein-associated phospholipase A2 (Lp-PLA2) has been proposed as an inflammatory marker of cardiovascular disease. In the present study, we investigated whether Lp-PLA2 is an independent predictor of coronary heart disease and ischemic stroke. Methods and Results— The Rotterdam Study is a population-based follow-up study in 7983 subjects ≥55 years of age. We performed a case-cohort study, including 308 coronary heart disease cases, 110 ischemic stroke cases, and a random sample of 1820 subjects. We used Cox proportional-hazard models with modification of the standard errors based on robust variance estimates to compute hazard ratios adjusted for age, sex, body mass index, systolic blood pressure, non-HDL cholesterol, HDL cholesterol, diabetes, smoking, alcohol consumption, cholesterol-lowering medication, white blood cell count, and C-reactive protein. Compared with the first quartile of Lp-PLA2 activity, multivariate-adjusted hazard ratios for coronary heart disease for the second, third, and fourth quartiles were 1.39 (95% CI, 0.92 to 2.10), 1.99 (95% CI, 1.32 to 3.00), and 1.97 (95% CI, 1.28 to 3.02), respectively ( P for trend=0.01). Corresponding multivariate-adjusted hazard ratios for ischemic stroke were 1.08 (95% CI, 0.55 to 2.11), 1.58 (95% CI, 0.82 to 3.04), and 1.97 (95% CI, 1.03 to 3.79) ( P for trend=0.03). The relation between Lp-PLA2 and coronary heart disease was present in both subjects with non-HDL cholesterol levels below the median and those with non-HDL cholesterol levels above the median. Conclusions— This study shows that Lp-PLA2 activity is an independent predictor of coronary heart disease and ischemic stroke in the general population.